2013
DOI: 10.1098/rsif.2013.0098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the infectious period distribution on predicted transitions in childhood disease dynamics

Abstract: The population dynamics of infectious diseases occasionally undergo rapid qualitative changes, such as transitions from annual to biennial cycles or to irregular dynamics. Previous work, based on the standard seasonally forced 'susceptible-exposed-infectious -removed' (SEIR) model has found that transitions in the dynamics of many childhood diseases result from bifurcations induced by slow changes in birth and vaccination rates. However, the standard SEIR formulation assumes that the stage durations (latent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
148
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(149 citation statements)
references
References 59 publications
1
148
0
Order By: Relevance
“…Because the mean latent period for measles (T lat ≃ 8 days, [1]) is long relative to the mean infectious period (T inf ≃ 5 days, [1]), it is natural to assume that the SEIR model will represent measles dynamics better than the simpler SIR model, which includes no latent period. However, Krylova & Earn [27] showed that the SIR model displays virtually identical dynamics to the SEIR if the length of the mean generation interval (≃13 days) is used for the mean infectious period in the SIR model. This dynamical correspondence holds also for versions of the SIR and SEIR model with realistically distributed stage durations, rather than the exponential distributions implied by equation (3.1) [27].…”
Section: Susceptible -Infectious -Recovered Versus Susceptibleexposedmentioning
confidence: 99%
See 4 more Smart Citations
“…Because the mean latent period for measles (T lat ≃ 8 days, [1]) is long relative to the mean infectious period (T inf ≃ 5 days, [1]), it is natural to assume that the SEIR model will represent measles dynamics better than the simpler SIR model, which includes no latent period. However, Krylova & Earn [27] showed that the SIR model displays virtually identical dynamics to the SEIR if the length of the mean generation interval (≃13 days) is used for the mean infectious period in the SIR model. This dynamical correspondence holds also for versions of the SIR and SEIR model with realistically distributed stage durations, rather than the exponential distributions implied by equation (3.1) [27].…”
Section: Susceptible -Infectious -Recovered Versus Susceptibleexposedmentioning
confidence: 99%
“…We use the simple sinusoidal forcing function (3.3) rather than more realistic term-time forcing [5,17] because the two yield virtually identical dynamics (for different a values) [5,27]. Introducing time-dependence into the transmission rate generally affects the basic reproduction number R 0 [30,31]; however, for the SIR model (3.1), inserting the mean transmission rate b 0 in place of b in equation (3.2) is correct [32].…”
Section: Seasonalitymentioning
confidence: 99%
See 3 more Smart Citations